Evaluating the Effectiveness of a Brief Mindful Self-Care and Resiliency (MSCR) Intervention for Nurses: a Controlled Trial - Slatyer, Susan; Craigie, M.; Heritage, B.; Davis, S.; Rees, Clare (2017)
It has been well documented that workplace stress can have a negative impact on nurse well-being and productivity, and can result in the syndrome of compassion fatigue, which is comprised of secondary traumatic stress and burnout. Identifying effective and practical workplace interventions to help improve nurse resilience to prevent compassion fatigue is therefore a high priority. This study trialled the effectiveness of a brief mindful self-care and resiliency intervention for nurses working in an Australian tertiary hospital compared to nurses in a wait list control condition. A total of 91 nurses participated in the study (n = 65 intervention condition; n = 26 control condition). The intervention involved a 1-day workshop followed by three weekly mindfulness practice sessions. Nurses completed measures of burnout, secondary traumatic stress, negative mood, self-compassion, compassion satisfaction, subjective quality of life and general self-efficacy at pre-test, post-test and 6-month follow-up. Analysis revealed that compared to the control group, the intervention group had significant reductions in burnout and depressed mood upon completion of the MSCR. Follow-up data indicated that these reductions persisted at 6-month post-MSCR for the intervention group. While interactions between intervention and control conditions for other measures failed to reach statistical significance, follow-up analysis revealed significant improvements in compassion satisfaction, self-compassion and subjective quality of life for nurses completing the intervention. As a whole, the findings demonstrate that a brief mindfulness-based self-care intervention is effective at improving the emotional functioning of nurses.